Intellectual capital and its relationship to the performance management of heads of scientific departments in the faculties of physical education and sports sciences (Global Scientific Review, 2025)
The importance of intellectual capital lies in the importance of knowledge and knowledge sharing, and that it is not important to possess knowledge, but rather how employees participate in managing that knowledge and using it in the organization’s various activities in a way that raises the level of performance and achieves continuous growth and success. Given the important role of human resources in the organization in the process of disseminating ideas, information and knowledge, especially in the field of practicing various human resources management activities, such as recruitment, training, development, compensation and employee performance management, interest in this resource and its management has increased significantly and it has come to be viewed as a strategic dimension and an important tool that has an important strategic role in the organization. Consequently, the research problem on which the study was premised could be stated as: What is the relationship between intellectual capital and performance management of heads of scientific branches in faculties of physical education and sports sciences? Prepare two measures of intellectual capital and performance management for heads of scientific branches in faculties of physical education and sports sciences. Identify intellectual capital and performance management for heads of scientific branches in faculties of physical education and sports sciences. To get the research data, construction and application samples are selected, and the research is conducted on them, as well as verifying their statistics in the third chapter and reaching the most important results, which are that intellectual capital contributes to influencing human resource management practices by employing the acquired value it achieves in building and developing these practices. Faculties of physical education and sports sciences can invest the acquired value in training and compensation practices and adopting employee performance management with the aim of raising the level of working individuals